Pengaruh Perputaran Modal Kerja Terhadap Profitabilitas Perusahaan - Satriya, I Made Dian; Lestari, Putu Vivi (E-Jurnal Manajemen, 2014)
Working capital required by each company to finance day-to- day operations , working capital which has been issued it is expected to be able to come back into the company in a short time through the sale of its production . Working capital role in sustaining operations or activities of the company , because without the working capital of a company's operations can not be run smoothly. This study aims to determine the effect of working capital turnover , cash turnover and inventory turnover to Profitability ( ROI ). This research was conducted on the property and real estate companies in Indonesia Stock Exchange ( IDX ) . The data used are secondary data from company financial statements of property and real estate . The population in this study is a Real Estate Property and sample period 2009-2011 and used a total of 12 samples from 43 companies . The technique of taking the sample using purposive sampling method . Analysis of data using multiple linear regression. The results showed that the variable rotation of working capital , cash turnover and inventory turnover has a positive and significant impact on profitability ( ROI ) . Keywords : working capital turnover , cash turnover , inventory turnover , profitability ( ROI )
Keywords: Working capital turnover , cash turnover , inventory turnover , profitability ( ROI )